2016
DOI: 10.1097/rlu.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Stroke Mimicking Cerebral Metastasis in 68Ga-PSMA-HBED-CC PET/CT

Abstract: A 65-year-old man with disseminated bone metastases of prostate cancer was referred for Ga-PSMA-HBED-CC-PET/CT (short PSMA-PET/CT) to exclude visceral metastases before treatment of bone metastases with Ra-dichloride. Apart from disseminated bone metastases, PSMA-PET/CT revealed a focal cerebral tracer uptake in the right frontal lobe highly suspicious for cerebral spread. According to patient history, a cerebral infarction occurred 14 days before PSMA imaging in corresponding localization confirmed by MRI sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…Some of the data from 76 patients in the present study have been analysed in previous studies on different topics [1820, 2426]. Patients without recurrent disease and patients who were referred for PSMA radioligand therapy were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the data from 76 patients in the present study have been analysed in previous studies on different topics [1820, 2426]. Patients without recurrent disease and patients who were referred for PSMA radioligand therapy were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…Since the late 1990s, it has been known that the neovasculature of many solid tumours also expresses PSMA [5]. Recently, there have been many reports of the uptake of PSMA ligands in various nonprostate tissues [618]. …”
Section: Introductionmentioning
confidence: 99%
“…There are ample studies utilizing PSMA-based imaging agents for tumor detection in prostate cancer (24)(25)(26)(27)(28)(29)(30)(31), high-grade gliomas (32)(33)(34)(35)(36) and lung BMs (33), as well as in follicular thyroid adenoma (37), metastatic renal cell carcinoma (38) and in melanoma and small cell lung cancer (SCLC) xenografts in vivo (39). However, recent reports showed that the cerebral radionecrotic uptake (40) or stroke (41) resulted in false positive diagnoses of cerebral metastases based on PSMA/CT uptake as limitation of the PSMA-based diagnostic glioma imaging. A single arm phase II study where PSMArecognizing ADC was used in progressive GBM patients (n = 6) following prior treatment with radiation, temozolomide, and bevacizumab showed no demonstrable activity in these patients (NCT01856933).…”
Section: Discussionmentioning
confidence: 99%
“…PSMA-PET/CT positivity seems to be a usual phenomenon in Paget disease [58] that should be taken into consideration when PSMA-PET/CT is used during workup of patients with prostate cancer in order to avoid a pitfall in this otherwise accurate and sensitive diagnostic tool [13]. Beside Paget disease, various other tumors [11], coeliac ganglia [12], splenosis [13], sarcoidosis [14], and subacute stroke [15] have been reported to cause false-positive PSMA-PET imaging findings.…”
Section: Discussionmentioning
confidence: 99%